Comparative Study Between PID Controller and Fuzzy Logic Controller for Robotic Hand - Mohd Mustapha, Nurul Hasyimah Binti Mohd Mustapha; Yaacob, Megat Satria Zainuddin (Progress in Engineering Application and Technology, 2021)
A controller is such a compliment to a system in order to let it working at a suitable specification. In this paper, Proportional-Integral-Derivative PID controller and Fuzzy logic controller are being compared to see which one has a better performance between them on a three fingers robotic hand application. MATLAB-Simulink used in this study to proceed with the simulation to obtain the results from the output graph. The simulation results demonstrate that PID controller realize a good behavior on the Robotic Hand, with less rise and settling time, minimum overshoot, and give better performance compared to Fuzzy Logic controller.